(untitled) (NPRC Journal of Multidisciplinary Research, 2025)
Background: The healthcare sector, while dedicated to healing, is a significant contributor to environmental degradation. The concept of "Green Healthcare" aims to resolve this contradiction by promoting sustainable practices that reduce the ecological footprint of healthcare delivery. In Nepal—a nation facing socio-economic disparities, climate vulnerability, and the challenge of building resilient systems—the role of future healthcare leaders is critical. This study investigates the readiness of undergraduate healthcare management (BHCM) students to drive this necessary transition, examining their awareness, attitudes, and practices regarding green healthcare. Objectives: This research aimed to: 1) Assess the level of awareness of green healthcare principles among BHCM students; 2) Evaluate their attitudes towards the role of sustainability in healthcare; and 3) Examine their current engagement in sustainable practices and advocacy. The study sought to identify the gap between knowledge, belief, and action. Methods: A quantitative, cross-sectional study was conducted among 205 undergraduate BHCM students from multiple colleges in Nepal, using a convenience sampling method. Data were collected via a structured online questionnaire with sections on demographics, awareness, attitudes, and practices, using a 5-point Likert scale. Analysis was performed using SPSS, employing descriptive statistics, one-sample t-tests, ANOVA, Pearson’s correlation, and Chi-square tests. Findings: Students demonstrated a significantly high level of theoretical awareness (mean score 3.91/5, p<.001) and uniformly positive attitudes across different academic backgrounds (no significant difference, p=.544). However, a distinct gap existed between this cognitive endorsement and consistent practical implementation. Positive correlations were found between awareness and practices (r=0.512, p<.01) and, more strongly, between practices and advocacy (r=0.569, p<.01). Gender showed no statistically significant association with core awareness. Conclusion: While the foundational awareness and positive attitudes essential for a green transition are firmly established, a tangible "green gap" in practical competency persists. The findings suggest that current education successfully homogenizes normative values but falls short in providing the context-specific, applied skills needed for implementation in Nepal’s unique setting. To build a truly inclusive and resilient health system, pedagogical reform is required to shift from creating universally aware graduates to empowering locally competent, practicing advocates for sustainable healthcare. Novelty: This study provides the first focused assessment of the Green Healthcare Awareness-Attitude-Practice (AAP) framework among future health system managers in Nepal. It uniquely frames the findings within critical sociological themes of inclusivity and resilience, arguing that bridging the "green gap" is not merely a technical educational challenge but a central component of preparing leaders who can advance environmental justice and equitable health system development.